Pesticides use and its impact on environment- The state of art (Funded Work) - SINGH BINDU; VIRENDRA KUMAR SINGH; KHALID MONOWAR ALAM (International Journal of Pharma and Bio Sciences, 2018)
Agriculture is the backbone of the economic system of a given country. In addition to providing food and raw material, agriculture also provides employment opportunities to very large percentage of the population. But today it is considered to be contaminated because pesticides are used worldwide to manage agricultural pests (a small animal or insect that destroys crops or food supplies).The worldwide use of these pesticides over the years has resulted in problems caused by their interaction with the biological system in the environment. They not only kill and repel unwanted pests but also cause many human deaths each year. Considering the toxic effect of pesticides, it is essential to remove these chemo-pollutants from the environment. Recently the use of microbes for effective detoxification, degradation, and removal of toxic compounds from contaminated soils has emerged as an efficient and cheap biotechnology approach to clean up the polluted environment. This review explores the widespread use of pesticides in agriculture and elaborates the potential application of various microorganisms in decontamination of agricultural soil.